Pengaruh Metode Think Pair Square dan Multimedia Driils Tehadap Berpikir Reflektif Mawaris - Rosyidi, Andri (Institut Agama Islam Yasni Bungo, 2024)
This research aims to find the impact of Think Pair Square and Multimedia Drills on the reflective thinking of IAI Yasni Bungo PAI Study Program students. This research was experimental. The population was all fifth-semester PAI study program students. The samples were the students of V A and V.B. The instruments used in this research were tests and questionnaire. The data in this study were analyzed using the t-test. The results of this research showed that (1) there is an impact of Think Pair Square on the reflective thinking of Mawaris, (2) there is an impact of multimedia drill on the reflective thinking of Mawaris, (3) there is an interaction of Think Pair Square and multimedia drills on the reflective thinking of Mawaris. Based on the results, Think Pair Square is an effective learning model for reflective thinking. In this case, Think Pair Square and multimedia drills can be reflective thinking strategies for PAI study program students.